The Only Way to Make a Friend - Lehman, Herbert H. (Tufts Archival Research Center, 2006)
Senator Lehman describes his two basic beliefs: First, one should give back to society according to what he or she has received, and secondly, one should extend respect to the opinions and beliefs of others.